Innovative technologies for gait and stance analysis - Seyfarth, A. (Sports technology. Fields of application, sports equipment and materials for sport, 2024)
The analysis of human movements has developed significantly in recent years. Mobile analysis systems are becoming more powerful due to ever cheaper and more accurate sensors and widespread mobile devices such as smartphones, and more convenient to use due to cross-system apps. In this chapter, the various analysis systems and measurement methods will be described and selected fields of research and application will be presented.